Neurodegenerative changes in Alzheimer’s disease: A review of anatomical features and histological findings - Mehdar, Khlood Mohammed (International Journal of Innovative Research and Scientific Studies, 2025)
Alzheimer’s disease (AD) is the leading cause of dementia worldwide, presenting an increasing challenge to healthcare systems due to its multivariate etiology and lack of curative therapeutic options. AD, first identified by Alois Alzheimer in 1907, is characterized by the buildup of amyloid beta (Aβ) peptides and hyperphosphorylated tau protein, which together generate the disease’s characteristic neuropathological lesions: amyloid plaques and neurofibrillary tangles (NFTs). The most prominent explanation regarding the pathophysiology of AD is still the amyloid cascade hypothesis, which postulates that neuronal malfunction and cognitive decline are caused by the aggregation of Aβ peptides into plaques. Elderly individuals with this condition typically exhibit progressive cognitive impairment and memory loss. Clinical assessment is the primary basis for diagnosis, which is complemented by modern imaging techniques such as positron emission tomography (PET) and cerebrospinal fluid (CSF) biomarkers. AD is characterized histologically by intracellular tangles and extracellular plaques that cause significant cerebral atrophy. Neurofibrillary tangles, composed of hyperphosphorylated tau, accumulate in neurons’ perikaryal cytoplasm, whereas senile plaques consist of a beta-amyloid core surrounded by dystrophic neurites. Other neuropathological signs include granulovacuolar degeneration and Hirano bodies. The synapse loss observed in AD has a significant impact on cognitive performance and exemplifies the disease’s extensive synaptic pathologies. It remains challenging to distinguish between early-stage AD and normal aging, particularly at advanced age. Recent treatment research focuses on altering the progression of the disease by targeting amyloid plaques and tau tangles, as well as developing early intervention options for individuals with preclinical AD or those at high risk of cognitive decline.